Extremely low-loss slow-light modes in plasmonic dielectric hybrid systems - Ishikawa, Atsushi; Oulton, Rupert F.; Zentgraf, Thomas; Zhang, Xiang (Plasmonics: Metallic Nanostructures and Their Optical Properties VIII)

Semiconductor plasmon laser - Sorger, Volker J.; Oulton, Rupert F.; Zentgraf, Thomas; Ma, Renmin; Gladden, Christopher; Dai, Lun; Bartal, Guy; Zhang, Xiang (Plasmonics: Metallic Nanostructures and Their Optical Properties VIII)

Individuelle Bildungsgänge im Berufsbildungssystem - Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Towards Model-based Acceptance Testing for Scrum - Löffler, Renate; Güldali, Baris; Geisen, Silke (Softwaretechnik-Trends)

Starthilfe für modellbasiertes Testen - Güldali, Baris; Jungmayr, Stefan; Mlynarski, Michael; Neumann, Stefan; Winter, Mario (OBJEKTspektrum)

Tabellarischer Vergleich der Prozessmodelle für modellbasiertes Testen aus Managementsicht - Beulen, Dominik; Güldali, Baris; Mlynarski, Michael (Softwaretechnik-Trends)

Agiles Testen in Großprojekten mit TDD und Testaspekten: Beobachtungen und erste Erfahrungen - Späth, Melanie; Mlynarski, Michael (Softwaretechnik-Trends)

Automated acceptance testing tools for web applications using Test-Driven Development - Jureczko, Marian; Mlynarski, Michael (Electrical Review)
In the last years the software engineering community pays a strong interest in agile development methods. Those methods place software testing for example the Test-Driven Development method as an important task of the development process. Agile projects rely on good test automation tools. In this paper we evaluate five test automation tools for their usage in acceptance testing for web applications using Test-Driven Development.

Rollenbasierte Kompetenzbilanz - Potenziale und Herausforderungen für das berufsschulische Übergangssystem - Frehe, Petra; Kremer, H.-Hugo (Funktionen und Erträge pädagogischer Diagnostik im wirtschafts- und berufspädagogischen Bereich)

Controlled Etching Behavior of O-Polar and Zn-Polar ZnO Single Crystals - Mehta, M.; Meier, Cedrik (Journal of The Electrochemical Society)

Electroluminescence from silicon nanoparticles fabricated from the gas phase - Theis, Jens; Geller, Martin; Lorke, Axel; Wiggers, Hartmut; Wieck, Andreas; Meier, Cedrik (Nanotechnology)

Model-Based Software Product Lines Testing Survey - Oster, Sebastian; Wübbeke, Andreas; Engels, Gregor; Schürr, Andy (Model-Based Testing For Embedded Systems)

Variabilitätsmanagement in Anforderungs- und Testfallspezifikation für Software-Produktlinien - Wübbeke, Andreas
Software Product Lines (SPL) are a development paradigm allowing the reduction of the software system development time while increasing their quality. To reach these goals, the artefacts being part of many or all software systems are developed only once and reused within the different software systems. The software systems developed by a software product line approach are called products. Like a thread the reuse of artefacts is woven into the software product line development process. As some artefacts are only used for the development of some products, these artefacts constitute the variability of the SPL. First of all, the modelling of variability has to be enabled in every artefact. Beside this, dependencies can arise between variable artefacts. The modelling of variability and dependencies also demands the redevelopment or adaption of specification techniques for these artefacts. This thesis focuses on the variability management concerning requirements and test case specification for Software Product Lines. For this purpose, existing modelling languages and specification techniques are augmented with variability instead of redeveloping similar software development artefacts over and over again. In order to augment the modelling languages by variability, a language construction process based on a meta model of the variability management is defined. In order to manage the dependencies between variable artefacts, a feature based variability management is introduced. Finally, the extension of specification techniques for requirements specifications based on use case descriptions and test specifications are described. The contribution of this thesis is substantiated by a prototypical tool support and an industrial case study.

Test-driven Language Derivation with Graph Transformation-based Dynamic Meta Modeling - Engels, Gregor; Soltenborn, Christian (Proceedings of the International Colloquium on Graph and Model Transformation (GraMoT 2010), Berlin (Germany))
Deriving a new language L_B from an already existing one L_A is a typical task in domain-specific language engineering. Here, besides adjusting L_A's syntax, the language engineer has to modify the semantics of L_A to derive L_B's semantics. Particularly, in case of behavioral modeling languages, this is a difficult and error-prone task, as changing the behavior of language elements or adding behavior for new elements might have undesired side effects. Therefore, we propose a test-driven language derivation process. In a first step, the language engineer creates example models containing the changed or newly added elements in different contexts. For each of these models, the language engineer also precisely describes the expected behavior. In a second step, each example model and its description of behavior is transformed into an executable test case. Finally, these test cases are used when deriving the actual semantics of L_B - at any time, the language engineer can run the tests to verify whether the changes he performed on L_A's semantics indeed produce the desired behavior. In this paper, we illustrate the approach using our graph transformation-based semantics specification technique Dynamic Meta Modeling. This is once more an example where the graph transformation approach shows its strengths and appropriateness to support software engineering tasks as, e.g., model transformations, software specifications, or tool development.

Agility vs. Model-based Testing: A fair Play? - Güldali, Baris; Mlynarski, Michael (Proceedings of the IWK2010 Workshops: The First International Workshop on Evolution Support for Model-Based Development and Testing (EMDT2010))

Verknüpfung von kombinatorischem Plattform- und individuellem Produkt-Test für Software-Produktlinien - Wübbeke, Andreas; Oster, Sebastian (Proceedings of Produktlinien im Kontext (PIK2010))

Towards Economical Software Release Recommendations - Sancar, Yavuz; Brüseke, Frank; Voigt, Hendrik; Sauer, Stefan; Engels, Gregor (ECOOP 2010 - Workshop on Testing Object-Oriented Software Systems (ETOOS))

A Framework for Change Management of Business Process Models - Gerth, Christian (Proceedings of the Joint Workshop of the German Research Training Groups in Computer Science)

Reusing Security Requirements using an Extended Quality Model - Luckey, Markus; Baumann, Andrea; Méndez Fernández, Daniel; Wagner, Stefan (Software Engineering for Secure Systems, 2010. SESS '10. ICSE Workshop)

Teststufenspezifische Qualitätsattribute für die Qualitätsbewertung von nichtfunktionalen Anforderungen - Sancar, Yavuz; Brüseke, Frank; Engels, Gregor (Proceedings of Software-Qualitätsmodellierung und -bewertung (SQMB '10), Paderborn, Germany)

Knowledge Transfer in Global Software Development - Leveraging Ontologies, Tools and Assessments - Salger, Frank; Sauer, Stefan; Engels, Gregor; Baumann, Andrea (5th IEEE International Conference on Global Software Engineering (ICGSE 2010))
To be successful with global software development (GSD), development knowledge needs to be shared among the developers and stakeholders, and the quality of the exchanged information must be assured. Therefore, mature processes, methods and tools have to be in place. If a unified and integrated solution does not exist, this impedes the exchange of knowledge (and the migration of people between projects). In GSD, such a diversity can lead to new problems: offshore development teams have to repeatedly re-adjust to method variants used by the respective business units. This can lead to misinterpretation of information and risks for project success. We report on re-aligning the varying software engineering methods and unifying the methodology throughout Capgemini sd&m. We also standardized quality assurance procedures and tightly integrated them with the engineering methodology. By this, we arrived at a comprehensive company-wide Enterprise Software Engineering Model that effectively supports knowledge transfer from clients to the onshore and offshore team.

MDDAUI 2010 Workshop Report - Van den Bergh, Jan; Meixner, Gerrit; Sauer, Stefan (Proc. 5th Intl. Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI 2010))

Pattern-based Generation of Test Plans for Open Distributed Processing Systems - Güldali, Baris; Sauer, Stefan; Winkelhane, Peter; Jahnich, Michael; Funke, Holger (Proceedings of 5th International Workshop on Automation of Software Test (AST 2010), ICSE Workshop)

Architecture-Driven Derivation of Performance Metrics - Brüseke, Frank; Sancar, Yavuz; Engels, Gregor (Proceedings of Software-Qualitätsmodellierung und -bewertung (SQMB '10), Paderborn, Germany)

Effort Comparison of Model-based Testing Scenarios - Güldali, Baris; Mlynarski, Michael; Sancar, Yavuz (Proceedings of 3th International Conference on Software Testing, Verification, and Validation Workshops)

Test Case Generation for Visual Contracts Using AI Planning - Schnelte, Matthias; Güldali, Baris (INFORMATIK 2010, Beiträge der 40. Jahrestagung der Gesellschaft für Informatik e.V. (GI))

Ultrasonically-assisted Hydrothermal Method for Ferroelectric Material Synthesis - Ageba, Ryo; Kadota, Yoichi; Maeda, Takafumi; Takiguchi, Norihito; Morita, Takeshi; Ishikawa, Mutsuo; Bornmann, Peter; Hemsel, Tobias (Journal of Korean Physical Society)
The hydrothermal method enables the production of high-quality piezoelectric materials. In this study, we propose to irradiate the reaction solutions with ultrasonic power during the hydrothermal method to obtain a shorter reaction time and a smooth film surface. A high-pressure reaction container for the ultrasonic transducer was newly developed, and the ultrasonically-assisted hydrothermal method was examined by using this container. The effect of ultrasonic assist on the synthesis of lead-zirconate-titanate (PZT) thin films and (K,Na)NbO$_{3}$ powders was verified. Thicker PZT film, thickness around 10 ${μ}$m, could be obtained in one process, and (K,Na)NbO$_{3}$ powder was synthesized in half the previous reaction time.
Keywords: Hydrothermal method; High-power ultrasonic; PZT thin film; Lead-free piezoelectric materials

Ultrasonic Transducer for the Hydrothermal Method - Bornmann, Peter; Hemsel, Tobias; Littmann, Walter; Ageba, Ryo; Kadota, Yoishi; Morita, Takeshi (Journal of Korean Physical Society)
Direct ultrasound irradiation is advantageous to increase the efficiency of the hydrothermal method which can be used for the production of piezoelectric thin films and lead free piezoelectric ceramics. To apply ultrasound directly to the process transducer prototypes were developed regarding the boundary conditions of the hydrothermal method. LiNbO$_{3}$ and PIC 181 were proven as feasible materials for high temperature resistant transducers ($≥ 200^° C$). Resistance of the transducers horn against the corrosive mineralizer was achieved by using Hastelloy C-22. The efficiency of the ultrasound assisted hydrothermal method depends on the generated sound field. Impedance and sound field measurements have shown that the sound field depends on the filling level and the position and design of the transducer.
Keywords: High-temperature transducer; Hydrothermal method; Lithium-niobate transducer

Modeling of Piezoelectric Langevin Transducers by Using Mixed Transfer Matrix Methods - Fu, Bo; Li, Chao; Zhang, Jianming; Huang, Zhenwei; Hemsel, Tobias (Journal of Korean Physical Society)
In the modeling of piezoelectric Langevin transducers using usual transfer matrix methods, some simplifications have been adopted. This leads to reduction of the model quality. A mixed transfer matrix method is employed in the modeling of Langevin transducers, where the pre-stressed bolt is modeled as a separate four-pole element, which is connected to other elements in parallel. Based on the mixed transfer matrix method, the four (six)-pole element description of the piezoelectric Langevin transducer is built up and the total transfer matrix relation is derived. The resonance frequencies of the transducer are calculated and then measured using the impedance analyzer (HP4192). Experimental result shows that the mixed transfer matrix method has better modeling quality than the usual transfer matrix method for the vibration analysis of piezoelectric Langevin transducers.
Keywords: Piezoelectric langevin transducer; Transfer matrix method; Four (six)-pole element description; Pre-stressed bolt

Reibungsdämpfung in ausgedehnten, verschraubten Fügestellen - Hölzl, Johannes Sebastian; Sextro, Walter (PAMM)
Bei der Konstruktion von Maschinen ist es oftmals erforderlich, Schwingungen minimal zu halten. Um z.B. die Lebensdauer zu erhöhen, Material einzusparen oder den Geräuschpegel gering zu halten muss oft ein großer Aufwand zur Dämpfung von auftretenden Schwingungen betrieben werden. In vielen technischen Anwendungen werden Einzelteile miteinander verschraubt. Diese Fügestellen können gezielt und mit wenig Aufwand zur Schwingungsdämpfung herangezogen werden. Die Berechnung des dynamischen Verhaltens verschraubter Strukturen stellt immer noch eine Herausforderung dar. Es wurde eine Methode entwickelt, um den eingeschwungenen Zustand elastischer, miteinander verschraubter Körper mit rauen Fügestellen bei periodischer Anregung zu berechnen. Als Basis dienen Finite Elemente Modelle der einzelnen Teile, deren Freiheitsgrade durch modale Kondensation reduziert werden. Unter Anwendung des Verfahrens von Ritz und Galerkin wird eine Näherungslösung für den eingeschwungenen Zustand des nichtlinearen, gekoppelten Systems ermittelt. Abhängig von den Schraubenvorspannkräften sowie den bestimmenden Parametern der Kontaktflächen, Rautiefe und Reibungskoeffizient, kann die Systemantwort berechnet und optimiert werden. Um die Berechnungsmethode zu verifizieren wurden Experimente durchgeführt. Der Vergleich zwischen Messung und Rechnung zeigt eine gute Übereinstimmung. ({©} 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim)

Simulation of the Dynamical Behavior of Elastic Multi-Body Systems with Bolted, Rough Contact Interfaces - Hölzl, Johannes Sebastian; Sextro, Walter (SAE International Journal of Passenger Cars- Mechanical Systems)
For many technical applications it is necessary to avoid or to reduce vibrations. Factors benefiting from vibration reduction are for example the durability of the application, which is increased, as well as cost expenses and the level of noise, which are both decreased. Rough, bolted interfaces are common in most machines and can be used as damping devices with some effort. Perhaps in future such contact surfaces could be used as damping devices at the interfaces of an automotive engine or exhaust system. Nevertheless it is difficult to predict the effect of a change in contact interface parameters on the dynamic behavior of the entire mechanical system. Therefore a method for calculating the steady state behavior of elastic multi-body systems was developed. The basis of this method is a finite element model of each contacting unit. On each model a modal reduction is applied in order to reduce the degrees of freedom. The method of Ritz and Galerkin is used to calculate the frequency response functions of the reduced system including contact. This method allows the calculation of the steady-state behavior of elastic multi-body systems with rough, bolted contact interfaces, by taking the pre-stress of the bolts, the roughness and the friction coefficient of the contacting surfaces as parameters. In order to verify calculated results, a test stand was built. The comparison of calculated and experimental results showed a satisfying correlation.
Keywords: Automotive

Various Aspects of the Placement of a Piezoelectric Material in Composite Actuators, Motors, and Transducers - Hemsel, Tobias; Lierk, Ernst Günther; Littmann, Walter; Morita, Takeshi (Journal of Korean Physical Society)
Piezoelectric materials find wide application in technical systems. Most often, a combination of piezoelectric and other materials is advantageous. The position and the amount of the piezoelectric material within the overall system depends on various aspects like maximum mechanical output to the load, maximum electromechanical efficiency of the system, maximum utilization of the piezoelectric material, minimum self-heating of the piezoelectric material, and controllability of the system, which might be key aspects for the optimisation of the system design. For a composite longitudinal vibrator (bolted Langevin transducer), which is a base for many technical applications, this contribution shows in detail, how above mentioned aspects depend on the position and volume of the piezoelectric material related to the mode shape.
Keywords: Bolted Langevin transducer; Optimum placement of piezoelectric ceramics

Intelligente mechatronische Systeme zur automatisierten Fahrzeugführung in Fahrerassistenzsystemen - Hess, D.; Hüfner, Thorsten; Hesse, Tobias; Sondermann-Wölke, Christoph; Sattel, Thomas (Internationales Mechatronik-Kolloquium "Mechatronik 2010")

Drive Signals for Maximizing the Velocity of Piezoelectric Inertia Motors - Hunstig, Matthias; Hemsel, Tobias (Journal of Korean Physical Society)
Piezoelectric inertia motors have a simple construction and are controlled by a single driving signal. This allows for miniaturization and low cost production. One of the main questions to be answered during the design process of a piezoelectric inertia motor is which electrical excitation signal yields optimum motor characteristics. Three signals and their variants are widely used in literature: sawtooth, parabolic and cycloidic signals. It can be shown that neither of these can drive the motor at its maximum possible velocity in non-resonant operation. Within this paper we propose to use a rigid body model of a simple inertia motor to predict the motor characteristics depending on the movement pattern of the driving element. Advantages and disadvantages of three different drive signals that maximize the motor velocity are discussed.

Parameter Identification and Model Validation for the Piezoelectric Actuator in an Inertia Motor - Hunstig, Matthias; Hemsel, Tobias (Journal of Korean Physical Society)
Piezoelectric inertia motors make use of the inertia of a slider to drive the slider by friction contact in a series of small steps which are generally composed of a stick phase and a slip phase. If the best electrical drive signal for the piezoelectric actuator in an inertia motor is to be determined, its dynamical behaviour must be known. A classic dynamic lumped parameter model for piezoelectric actuators is valid only in resonance and, therefore, is not suitable for modelling the actuator in an inertia motor. A reduced dynamic model is used instead. Its parameters are identified using a step response measurement. This model is used to predict the movement of the actuator in response to a velocity-optimized signal introduced in a separate contribution. Results show that the model cannot represent the dynamical characteristics of the actuator completely. For determining voltage signals that let piezoelectric actuators follow a calculated movement pattern exactly, the model can, therefore, only be used with limitations.

Anregungskonzepte und Modellierung piezoelektrischer Trägheitsmotoren - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (7. Paderborner Workshop Entwurf mechatronischer Systeme)
Piezoelektrische Trägheitsmotoren nutzen die Trägheit einer bewegten Masse, um diese in kleinen Schritten durch abwechselnde Haft- und Gleitphasen voranzutreiben. Eine Kernfrage bei der Entwicklung eines piezoelektrischen Trägheitsmotors ist, welches elektrische Ansteuersignal für das gewünschte Motorverhalten optimal ist. Das elektrische Signal führt zu einer Bewegung des piezoelektrischen Aktors und damit der Antriebsstange, die den reibschlüssigen Vortrieb bewirkt. Entsprechend wird diese Fragestellung in zwei Teilen untersucht: Anhand eines Starrkörpermodells werden zunächst Bewegungsverläufe für die Antriebsstange ermittelt, mit denen die maximale Geschwindigkeit erreicht wird. Dabei werden drei Antriebsmodi identifiziert. Mit allen kann eine höhere Geschwindigkeit als mit der heute häufig verwendeten Sägezahnanregung erreicht werden. Anschließend wird ein einfaches dynamisches Modell eines piezoelektrischen Aktors genutzt, um die notwendigen elektrischen Ansteuersignale für die verschiedenen Antriebsmodi zu bestimmen. Es zeigt sich, dass das gewählte einfache Modell hierzu nur bedingt geeignet ist.
Keywords: Piezoelektrischer Trägheitsmotoren

Improving the Performance of Piezoelectric Inertia Motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (ACTUATOR 2010 Conference Proceedings)
A model based design approach for improved piezoelectric inertia motors is presented. Three velocityoptimized movement patterns for the driving body have been derived. The influence of the motor parameters and the process of designing an application specific motor with maximum velocity are shown. A simple dynamic model of the piezoelectric actuator is used to calculate the voltage signal for achieving the desired movement pattern. Observed distortions of the optimum pattern, their influence on the motion of the driven body and different methods to reduce them are discussed.

Konzeption und Aufbau eines Langzeitforschungsstandes zur lichttechnischen Charakterisierung von organischen Leuchtdioden (OLEDs) - Kraft , Verena; Bauch, C.; Nückel, M.; Hemsel, Tobias (19. Gemeinschaftstagung LICHT 2010)

Zur Theorie der piezoelektrischen Ultraschallverbundschwinger mit praktischen Schlussfolgerungen für den Entwicklungsingenieur - Lierke, Ernst-Günter; Littmann, Walter; Hemsel, Tobias (Veröffentlichung der Universität Paderborn)
Dieser Beitrag fasst die bekannten analytischen Berechnungsmethoden für piezoelektrische Ultraschallverbundschwinger zusammen und gibt anhand typischer Beispiele Anleitungen zur Lösung theoretischer und technischer Fragen bei deren Entwicklung. Zunächst werden die passiven, in der Regel metallischen Komponenten von Verbundschwingern als Stab- oder Plattensysteme mit homogen verteilten Feder-, Masse und Dämpfungseigenschaften beschrieben. Hier breitet sich die Schwingungsenergie in Form stehender und fortschreitender Wellen zum akustischen Verbraucher hin aus. Es folgt eine gleichwertige und schaltungstreue Darstellung durch elektrische oder mechanische Vierpole, die für den Entwicklungsingenieur leichter zu handhaben sind und in Netzwerken direkt mit Masons Ersatzschaltung des piezoelektrischen Wandlers gekoppelt werden können. Danach werden die wichtigsten, messtechnisch zugänglichen Parameter anhand eines in Resonanznähe zulässigen Ersatzmodells mit konzentrierten elektrischen bzw. mechanischen Komponenten definiert. Als Schwerpunkt wird anschließend deren analytische Berechnung und messtechnische Verifizierung an typischen Beispielen demonstriert. Es folgen wichtige technische Informationen über Frequenzkorrekturen, Schallgeschwindigkeitsdispersion, Leistungs- und Belastbarkeitsgrenzen der Komponenten und andere wertvolle praktische Hinweise.

The experimental research of piezoelectric actuator with two vectors of polarization direction - Lucinskis, Raimundas; Mazeika, Dalius; Hemsel, Tobias; Bansevicius, Ramutis (MECHANIKA)

Hydrothermal (K1-xNax)NbO3 Lead-free Piezoelectric Ceramics - Maeda, Takafumi; Takiguchi, Norihito; Morita, Takeshi; Ishikawa, Mutsuo; Hemsel, Tobias (Journal of Korean Physical Society)
As a lead-free piezoelectric ceramics, (K,Na)NbO$_{3}$ is a promising material because of its good piezoelectric properties. In this study, (K$_{1-x}$Na$_{x}$)NbO$_{3}$ ceramics were synthesized from a KNbO$_{3}$ and NaNbO$_{3}$ mixture powder prepared by the hydrothermal reaction. The hydrothermal reaction enables the production of high quality powder for the ceramics fabrication process. To obtain (K$_{1-x}$Na$_{x}$)NbO$_{3}$ ceramics, these two powders KNbO$_{3}$ and NaNbO$_{3}$ were mixed and then sintered together. X-Ray diffraction analysis revealed that the solid solution ceramics (K$_{1-x}$Na$_{x}$)NbO$_{3}$ was produced by the sintering process. The K/Na ratio in (K$_{1-x}$Na$_{x}$)NbO$_{3}$ ceramics was optimized for the best piezoelectric properties. The optimized forms was (K$_{0.48}$Na$_{0.52}$)NbO$_{3}$, which showed the following piezoelectric properties; k$_{33}$=0.56, d$_{33}$=114pC/N. In addition, the ferroelectric properties, P$_{r}$=7.72mC/cm$^{2}$, E$_{c}$=857V/mm, and the Curie temperature T$_{c}$=420$_{o}$C were also measured.
Keywords: Lead-free piezoelectric material; KNN; Hydrothermal method

(K,Na)NbO3 lead-free piezoelectric ceramics synthesized from hydrothermal powders - Maeda, Takafumi; Takiguchi, Norihito; Morita, Takeshi; Ishikawa, Mutsuo; Hemsel, Tobias (Materials Letters)
Among various lead-free piezoelectric materials, (K,Na)NbO$_{3}$ is a very promising candidate. In this study, (K,Na)NbO$_{3}$ ceramics were sintered from mixed (K,Na)NbO$_{3}$ and NaNbO$_{3}$ powders prepared by hydrothermal reaction. These two powders were mixed with distilled water in a KNbO$_{3}$/NaNbO$_{3}$ molar ratio of 1. After sintering the mixed powder, the solid solution of (Na,K)NbO$_{3}$ ceramics was obtained. The electrical properties such as the electromechanical coupling factors k$_{p}$ and k$_{33}$, the mechanical quality factor, Q$_{m}$, and the piezoelectric constant d$_{33}$ of the sintered (K,Na)NbO$_{3}$ ceramics were 0.32, 0.48, 71 (radial mode), 118 ((33)mode), and 107 pC/N, respectively.
Keywords: Lead-free piezoelectric material; (K; Na)NbO$_{3}$ ceramics; Sintering solid solution; Piezoelectric properties

Guideline for the dependability-oriented design of self-optimizing systems - Sondermann-Wölke, Christoph; Hemsel, Tobias; Sextro, Walter; Gausemeier, Jürgen; Pook, Sebastian (Industrial Informatics (INDIN), 2010 8th IEEE International Conference on)
Self-optimizing systems are able to adapt their behavior autonomously according to their current self-determined objectives. Unforeseen influences could lead to dependability-critical behavior of the system. Methods are required which secure self-optimizing systems during operation. These methods to increase the dependability of the system should already be taken into consideration in the design process. This paper presents a guideline for the dependability-oriented design of self-optimizing systems, which integrates established classical methods like failure mode and effects analysis as well as methods based on self-optimization. On the one hand self-optimization is used to increase the dependability of the system by integrating objectives like safety, availability, and reliability to the objectives of the system. On the other hand methods are required to ensure the self-optimization itself. As basis for this guideline serves the principle solution of the system. The six phases of the guideline extend the design process and lead to an enhanced principle solution. Additionally, the guideline illustrates phases to implement and validate the self-optimizing system. The proposed guideline is applied to an innovative rail-bound vehicle, called RailCab, which is equipped with self-optimizing function modules.
Keywords: RailCab; dependability-critical behavior; dependability-oriented design; failure mode; rail-bound vehicle; secure self-optimizing systems; self-optimizing function modules; optimisation; railways; self-adjusting systems

Integration of Condition Monitoring in Self-optimizing Function Modules Applied to the Active Railway Guidance Module - Sondermann-Wölke, Christoph; Sextro, Walter (International Journal On Advances in Intelligent Systems)
New mechatronic systems, called self-optimizing systems, are able to adapt their behavior according to environmental, user and system specific influences. Self-optimizing systems are complex and due to their non-deterministic behavior comprise hidden risks, which cannot be foreseen in the design phase of the system. Therefore, modifications of the ISO 17359 condition monitoring policy for being able to cope with this new kind of systems are presented. Besides avoiding critical situations evoked by self-optimization, the proposed concept uses self-optimization to increase the dependability of the system. This concept is applied to the active guidance module of an innovative rail-bound vehicle. First test drives provide information for the enhancement of the implementation of realtime switching to appropriate control strategies. The different control strategies are investigated in detail. It is illustrated that influences on the system like different track sections or the desired velocity of the RailCab effect the system and can lead to a higher amount of flange contacts, which indicate higher wear and thus a reduction of the availability of the system. Therefore, these influences should be minded within the condition monitoring policy. Consequently, this article presents the condition monitoring policy for self-optimizing function modules and its application to the active railway guidance module.
Keywords: dependability; condition monitoring; selfoptimization; active railway guidance module

Experimentelle Untersuchung der Selbstoptimierung innerhalb des RailCab-Spurführungsmoduls - Sondermann-Wölke, Christoph; Sextro, Walter; Geisler, Jens; Trächtler, Ansgar (Entwurf mechatronischer Systeme)
Die erweiterten Möglichkeiten der Informationsverarbeitung mechatronischer Systeme erlauben es, mechatronische Systeme selbstoptimierend zu gestalten. Dabei bezieht sich die Selbstoptimierung auf die Fähigkeit des Systems, sich an die aktuelle Umfeldsituation anzupassen; wobei das System im Allgemeinen mehrere relevante Ziele verfolgt. Wurde eine Umfeldveränderung bemerkt, so müssen diese Ziele an die neue Situation angepasst und das resultierende Verhalten ausgewählt werden. In diesem Beitrag wird das selbstoptimierende Spurführungsmodul näher untersucht. Das Spurführungsmodul ist Bestandteil eines innovativen schienengebundenen Verkehrssystems, genannt RailCab, und dient zur Lenkung des einzelnen Fahrzeugs. Ziele des Spurführungsmoduls bestehen darin, die Verlässlichkeit des Spurführungsmoduls zu erhöhen sowie möglichst wenig Energie zu verbrauchen. Um kritische Systemzustände zu erkennen bzw. frühzeitig zu verhindern wird eine Vorgehensweise zur Einrichtung einer Zustandsüberwachung für selbstoptimierende Systeme beschrieben. Diese wird auf dem realen Versuchsträger im Maßstab 1:2,5 implementiert. Die Auswertung von Versuchsfahrten zeigt, dass gerade beim Auftreten eines Fehlers das Umschalten vom Ziel ''Energieverbrauch minimieren`` auf das Ziel ''Verlässlichkeit maximieren`` sinnvoll ist.
Keywords: Selbstoptimierung; Spurführungsmodul

Increasing the reliability of a self-optimizing railway guidance system - Sondermann-Wölke, Christoph; Geisler, Jens; Sextro, Walter (Reliability and Maintainability Symposium (RAMS), 2010 Proceedings - Annual)
Recent advances in information processing enable new kinds of technical systems, called self-optimizing systems. These systems are able to adapt their objectives and their behavior according to the current situation and influences autonomously. This behavior adaptation is non-deterministic and hence self-optimization is a risk to the system, e.g. if the result of the self-optimization process does not match the suddenly changed situation. In contrary, self-optimization could be used to increase the dependability by pursuing objectives like reliability and availability. In our preceding publications we introduced the so called multi-level dependability concept to cope with this new kind of systems (cf. [6]). This concept comprises the monitoring of the system behavior, the classification of the current situation, and the selection of the appropriate measure, if reliability limits are exceeded. In this paper we present for the first time experimental results. The dependability concept is implemented in the self-optimizing active guidance system of a railway vehicle. The test drives illustrate clearly that the proposed concept is able to cope with, e.g., sensor failures, and is able to increase the reliability and availability of the active guidance module.
Keywords: availability; dependability concept; multilevel dependability concept; railway vehicle; reliability; self optimizing active guidance system; self optimizing railway guidance system; situation classification; system behavior monitoring; optimal control; railways; reliability theory; self-adjusting systems

Einfluss von Oberflächenrauheit, fluiden Zwischenschichten und Kontakttemperaturen auf den Kraftschluss zwischen Rad und Schiene - Tomberger, Christoph; Dietmaier, Peter; Martin, Rosenberger; Sextro, Walter; Six, Klaus (ZEVrail)

Phonon-mediated relaxation in doped quantum dot molecules - Grodecka-Grad, Anna; Förstner, Jens (Journal of Physics: Conference Series)
We study a single quantum dot molecule doped with one electron in the presence of electron-phonon coupling. Both diagonal and off-diagonal interactions representing real and virtual processes with acoustic phonons via deformation potential and piezoelectric coupling are taken into account. We employ a non-perturbative quantum kinetic theory and show that the phonon-mediated relaxation is dominated by an electron tunneling on a picosecond time scale.A dependence of the relaxation on the temperature and the strength of the tunneling coupling is analyzed.
Keywords: tet_topic_qd

Growth of cubic GaN on nano-patterned 3C-SiC/Si (001) substrates - Kemper, R.M.; Weinl, M.; Mietze, C.; Häberlen, M.; Schupp, T.; Tschumak, E.; Lindner, Jörg; Lischka, K.; As, Donald (Journal of Crystal Growth)
Non-polar relaxed cubic GaN was grown by molecular beam epitaxy (MBE) on nano-patterned 3C-SiC/Si (0 0 1)substrates with negligible hexagonal content and less defect density than in planar cubic GaN layers.Nano-patterning of 3C-SiC/Si(001) is achieved by self-ordered colloidal masks for the first time. The method presented here offers the possibility to create nano-patterned cubic GaN without the need for a GaN etching process andt hus isa potential alternative to the conventional top–down fabrication techniques.

Plasma modification of nanosphere lithography masks made of polystyrene beads - Gogel, D.; Weinl, M.; Lindner, Jörg; Stritzker, B. (JOURNAL OF OPTOELECTRONICS AND ADVANCED MATERIALS)
Nanosphere lithography (NSL) masks consisting of mono- or double-layers of polystyrene (PS) nano-beads are fabricated on silicon exploiting the self-organization of PS particles during the controlled drying of a colloidal suspension on a surface. The shape changes and shrinkage of PS sphere masks upon treatment in an air plasma are studied as a function of initial sphere size, plasma power and treatment time. The influence of several experimental parameters, including the plasma induced temperature rise, are analysed using scanning and transmission electron microscopy. It is demonstrated that a variety of new intriguing nanopatterns can be generated on silicon surfaces by the combination of NSL and plasma techniques, largely broadening the variety of patterns available so far by NSL.

On the equivalence of Nash and evolutionary equilibrium in finite populations - Hehenkamp, Burkhard; Possajennikov, Alex; Guse, Tobias (Journal of Economic Behavior & Organization)

Strategic Unemployment - Angerhausen, Julia; Bayer, Christian; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics (JITE))

Theory of phonon-mediated relaxation in doped quantum dot molecules - Grodecka-Grad, A.; Förstner, Jens (Physical Review B)
A quantum dot molecule doped with a single electron in the presence of diagonal and off-diagonal carrierphonon couplings is studied by means of a nonperturbative quantum kinetic theory. The interaction with acoustic phonons by deformation potential and piezoelectric coupling is taken into account. We show that the phonon-mediated relaxation is fast on a picosecond time scale and is dominated by the usually neglected off-diagonal coupling to the lattice degrees of freedom leading to phonon-assisted electron tunneling. We show that in the parameter regime of current electrical and optical experiments, the microscopic non-Markovian theory has to be employed.
Keywords: tet_topic_qd

Nonpolar cubic AlGaN/GaN heterojunction field-effect transistor on Ar+ implanted 3C–SiC (001) - Tschumak, E.; Granzner, R.; Lindner, Jörg; Schwierz, F.; Lischka, K.; Nagasawa, H.; Abe, M.; As, Donald (Applied Physics Letters)
A heterojunction field-effect transistor (HFET) was fabricated of nonpolar cubic AlGaN/GaN grown on Ar+ implanted 3C–SiC (001) by molecular beam epitaxy. The device shows a clear field effect at positive bias voltages with V_th=0.6 V. The HFET output characteristics were calculated using ATLAS simulation program. The electron channel at the cubic AlGaN/GaN interface was detected by room temperature capacitance-voltage measurements.

Reentrant superconductivity in superconductor/ferromagnetic-alloy bilayers - Zdravkov, V. I.; Kehrle, J.; Obermeier, G.; Gsell, S.; Schreck, M.; Müller, C.; Krug von Nidda, H.-A.; Lindner, Jörg; Moosburger-Will, J.; Nold, E.; Morari, R.; Ryazanov, V. V.; et al. (Physical Review B)
We studied the Fulde-Ferrell-Larkin-Ovchinnikov-type state established due to the proximity effect in superconducting Nb/Cu_41Ni_59 bilayers. Using a special wedge-type deposition technique, series of 20–35 samples could be fabricated by magnetron sputtering during one run. The layer thickness of only a few nanometers, the composition of the alloy, and the quality of interfaces were controlled by Rutherford backscattering spectrometry, high-resolution transmission electron microscopy, and Auger spectroscopy. The magnetic properties of the ferromagnetic alloy layer were characterized with superconducting quantum interference device magnetometry. These studies yield precise information about the thickness and demonstrate the homogeneity of the alloy composition and magnetic properties along the sample series. The dependencies of the critical temperature on the Nb and Cu41Ni59 layer thickness, T_c(d_S) and T_c(d_F), were investigated for constant thickness d_F of the magnetic alloy layer and d_S of the superconducting layer, respectively. All types of nonmonotonic behaviors of T_c versus d_F predicted by the theory could be realized experimentally, from reentrant superconducting behavior with a broad extinction region to a slight suppression of superconductivity with a shallow minimum. Even a double extinction of superconductivity was observed, giving evidence for the multiple reentrant behavior predicted by theory. All critical temperature curves were fitted with suitable sets of parameters. Then, T_c(d_F) diagrams of a hypothetical ferromagnet/superconductor/ferromagnet spin-switch core structure were calculated using these parameters. Finally, superconducting spin-switch fabrication issues are discussed in detail in view of the achieved results.

Characterization of unintentional doping in nonpolar GaN - Zhu, Tongtong; Johnston, Carol F.; Häberlen, Maik; Kappers, Menno J.; Oliver, Rachel A. (Journal of Applied Physics)
Unintentional doping in nonpolar a-plane 112¯0 gallium nitride GaN grown on r-plane 11¯02 sapphire using a three-dimensional 3D–two-dimensional 2D growth method has been characterized. For both 2D only and 3D–2D growth, the presence of an unintentionally doped region adjacent to the GaN/sapphire interface is observed by scanning capacitance microscopy SCM. The average width of this unintentionally doped layer is found to increase with increasing 3D growth time. By using an intentionally doped GaN:Si staircase structure for calibration, it is shown that the unintentionally doped region has an average carrier concentration of 2.50.31018 cm−3. SCM also reveals the presence of unintentionally doped features extending at 60° from the GaN/sapphire interface. The observation of decreasing carrier concentration with distance from the GaN/sapphire interface along these features may suggest that the unintentional doping arises from oxygen diffusion from the sapphire substrate. Low temperature cathodoluminescence spectra reveal emission peaks at 3.41 and 3.30 eV, which are believed to originate from basal plane stacking faults BSFs and prismatic stacking faults PSFs, respectively. It is shown that the inclined features extending from the GaN/sapphire interface exhibit both enhanced BSF and PSF emission. We suggest that enhanced unintentional doping occurs in regions around PSFs. Where BSFs intersect this doped material their emission is also enhanced due to reduced nonradiative recombination. Transmission electron microscopy confirms the presence of PSFs extending through the film at 60° from the GaN/sapphire interface.

Defects in carbon implanted silicon calculated by classical potentials and first-principles methods - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, Jörg; Schmidt, W. G.; Rauls, E. (Physical Review B)
A comparative theoretical investigation of carbon interstitials in silicon is presented. Calculations using classical potentials are compared to first-principles density-functional theory calculations of the geometries, formation, and activation energies of the carbon dumbbell interstitial, showing the importance of a quantummechanical description of this system. In contrast to previous studies, the present first-principles calculations of the interstitial carbon migration path yield an activation energy that excellently matches the experiment. The bond-centered interstitial configuration shows a net magnetization of two electrons, illustrating the need for spin-polarized calculations.

Advanced topics and applications of Transmission Electron Microscopy, Part I-II - Lindner, Jörg

Ion Beams and Nano-Engineering

Dislocation reduction in MOVPE grown GaN layers on (111)Si using SiNxand AlGaN layers - Häberlen, M; Zhu, D; McAleese, C; Kappers, M J; Humphreys, C J (Journal of Physics: Conference Series)
Growth of GaN on Si(111) potentially enables cost efficient manufacturing of optoelectronic devices due to the possibility of using cheap large area substrates. However, GaN layers grown on Si(111) substrates suffer from high tensile stress that can lead to cracking at layer thicknesses exceeding 1 μm. Another challenge is the high dislocation density of GaN layers grown on Si(111) which is detrimental to device performance. In this paper we show that a step graded AlGaN buffer layer can compensate tensile stress, avoiding cracking, and at the same time reduce the dislocation density. An additional SiNx interlayer in the GaN layer is shown to further reduce the dislocation density down to the high 108 /cm². Weak beam dark field TEM was used to study the dislocation reduction in cross sectional samples and for comparison of the step graded AlGaN buffer layer structure to a continuously graded one. STEM ADF was used to determine the exact location of dislocation bending with respect to the position of the interface.

Dislocation reduction in GaN grown on Si(111) using a strain-driven 3D GaN interlayer - Häberlen, Maik; Zhu, Dandan; McAleese, Clifford; Zhu, Tongtong; Kappers, Menno J.; Humphreys, Colin J. (physica status solidi (b))
In this paper we demonstrate a strain-driven GaN interlayer method to reduce dislocation densities in GaN grown on (111) oriented silicon by metal organic vapour phase epitaxy (MOVPE). In order to achieve crack-free GaN layers of reasonable thicknesses and dislocation densities it is crucial to integrate both dislocation reduction and strain management layers. In contrast to techniques like FACELO or nanoELO we show the in situ formation of GaN islands directly on the AlN nucleation layer without the need to deposit a SiO2 or SiNx mask. A graded AlGaN layer for strain management can be grown on top of this dislocation reducing 3D GaN inter-layer in order to achieve crack-free GaN layers grown on top of the AlGaN strain management layer. Furthermore, an additional SiNx layer for subsequent dislocation reduction can also be incorporated into the structure and is shown to efficiently reduce the dislocation density down to the low 10^9 cm^2. The structural properties of the 3D GaN island buffer layer and overgrown samples are studied by means of SEM, cross-sectional, and plan view TEM. Cathodoluminiscence in an SEM is employed to correlate the dislocation microstructure as observed by plan view TEM with luminescent properties.

Low temperature photoluminescence and cathodoluminescence studies of nonpolar GaN grown using epitaxial lateral overgrowth - Häberlen, M.; Badcock, T. J.; Moram, M. A.; Hollander, J. L.; Kappers, M. J.; Dawson, P.; Humphreys, C. J.; Oliver, R. A. (Journal of Applied Physics)
Low temperature cathodo- and photoluminescence has been performed on nonpolar a-plane GaN films grown using epitaxial lateral overgrowth. In films overgrown at a low V–III ratio, the emission spectrum is dominated by “yellow” and “blue” luminescence bands, attributed to recombination at point defects or impurities. The intensity of this emission is observed to decrease steadily across the window region along the −c direction, possibly due to asymmetric diffusion of a point defect/impurity species. When overgrown at a higher V–III ratio, the near band edge and basal-plane stacking fault emission intensity increases by orders of magnitude and a donor–acceptor pair band is observed. Using monochromatic cathodoluminescence imaging, the various emission features are correlated with the microstructure of the film. In particular, the peak energy of the basal-plane stacking fault emission is seen to be blueshifted by 15 meV in the wing relative to the window region, which may be related to the different strain states in the respective regions.

The effects of annealing on non-polar (112¯0) a-plane GaN films - Hao, Rui; Zhu, T.; Häberlen, M.; Chang, T.Y.; Kappers, M.J.; Oliver, R.A.; Humphreys, C.J.; Moram, M.A. (Journal of Crystal Growth)
Non-polar a -plane (1 1 2 ̄ 0) GaN films were grown on r-plane sapphire by metal–organic vapor phase epitaxy and were subsequently annealed for 90 min at 1070°C. Most dislocations were partial dislocations, which terminated basal plane stacking faults. Prior to annealing, these dislocations were randomly distributed. After annealing, these dislocations moved into arrays oriented along the [0 0 0 1] direction and aligned perpendicular to the film–substrate interface throughout their length, although the total dislocation density remained unchanged. These changes were accompanied by broadening of the symmetric X-ray diffraction 1 1 2 ̄ 0 w-scan widths. The mechanism of movement was identified as dislocation glide, occurring due to highly anisotropic stresses (confirmed by X-ray diffraction lattice parameter measurements) and evidenced by macroscopic slip bands observed on the sample surface. There was also an increase in the density of unintentionally n-type doped electrically conductive inclined features present at the film–substrate interface (as observed in cross-section using scanning capacitance microscopy), suggesting out-diffusion of impurities from the substrate along with prismatic stacking faults. These data suggest that annealing processes performed close to film growth temperatures can affect both the microstructure and the electrical properties of non-polar GaN films.

Fine Structure of Triplet Centers in Room Temperature Irradiated 6H-SiC - Scholle, Andreas; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
In non-annealed 6H-SiC samples that were electron irradiated at room temperature, a new EPR signal due to a S=1 defect center with exceptionally large zero-field splitting (D = +652·10-4 cm-1) has been observed under illumination. A positive sign of D demonstrates that the spin-orbit contribution to the zero-field splitting exceeds by far that of the spin-spin interaction. A principal axis of the fine structure tilted by 59° against the crystal c-axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin-orbit coupling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

TCO-as-a-Service --- Servicebasierte Lebenszyklusrechnung für hybride Leistungsbündel - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver; Müller, Steffen (Vertriebsinformationssysteme --- Standardisierung, Individualisierung, Hybridisierung und Internetisierung)

E-Services im Handel --- Auffindung und Dokumentation von Potenzialen zur Digitalisierung von Dienstleistungen für Hersteller und Kunden - Beverungen, Daniel; Knackstedt, Ralf; Winkelmann, Axel (Vertriebsinformationssysteme --- Standardisierung, Individualisierung, Hybridisierung und Internetisierung)

Vermarktung hybrider Leistungsbündel - Weddeling, Matthias; Steiner, Michael; Müller, Oliver; Knackstedt, Ralf; Becker, Jörg; Backhaus, Klaus; Beverungen, Daniel; Frohs, Margarethe

PAS 1091: Schnittstellenspezifikationen zur Integration von Sach- und Dienstleistung. - Institut für Normung e.V., Deutsches

Handels- und steuerrechtliche Kapitalkontenfortschreibung und deren Einfluss auf die Verlustverrechnung bei Personengesellschaften - Kopplin, Anja; Maßbaum, Alexandra; Sureth-Sloane, Caren (Die Wirtschaftsprüfung)

Der Einfluss von Thin Capitalization Rules auf unternehmerische Kapitalstrukturentscheidungen - Maßbaum, Alexandra

Empirische Analyse der Unternehmensbewertung für die Erbschaftsteuer mit dem vereinfachten Ertragswertverfahren - Müller, Jens; Sureth-Sloane, Caren

Mögliche Fallstricke einer Optimierung unternehmerischer Investitionsentscheidungen auf der Grundlage der Konzernsteuerquote - Müller, Jens; Sureth-Sloane, Caren; Läufer, Christian (Die Wirtschaftsprüfung)

The Impact of Profit Taxation on Capitalized Investment with Options to Delay and Divest - Schneider, Georg; Sureth-Sloane, Caren

Beteiligungsveräußerungen und Abgeltungssteuer - Sureth-Sloane, Caren (Besteuerung, Rechnungslegung und Prüfung der Unternehmen)

Wichtigste Einflussfaktoren auf die steuerliche Verlustnutzung bei Personengesellschaften - Sureth-Sloane, Caren (Steuer und Studium)

Welchen Einfluss hat die Anwesenheit von ausländischen und multinationalen Unternehmungen auf die deutschen Exporte? - Gilroy, Bernard Michael; Lukas, Elmar; Heimann, Christian

Effizienz Deutscher Krankenhäuser im Zeitablauf - Schmitz, Hendrik; Augurzky, B.

Die Wirkung ausländischer Direktinvestitionen auf die Beschäftigung im Heimatmarkt: Eine empirische Analyse des deutschen Mittelstands. - Zapkau, F B; Schwens, C; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Enlarging the Focus on the Role of Competencies, Abilities, and Personality in Management Research. - Steinmetz, Holger; Schwens, C; Isidor, R; Kabst, Rüdiger (Management Revue: The International Review of Management Studies.)

Internationalisierung junger Technologieunternehmen: Auslandsmärkte und Erfolgsimplikationen. - Schwens, C; Kabst, Rüdiger (Die Betriebswirtschaft (DBW).)

Subjective Health and its Relationship with Working Time and Job Stressors: Sequence or General Factor Model?. - Steinmetz, Holger; Schmidt, P (Work and Stress.)

Measuring eTrust in distributed systems - General Concept and Application to Internet Voting - Volkamer, Melanie; Schryen, Guido (Proceedings of the 23rd Bled eConference)
Emerging digital environments and infrastructures, such as distributed services and computing services, have generated new options of communication, information sharing, and resource utilization in past years. Different distributed trust concepts are applied to increase trust in such systems. However, these concepts yield to rather complex architectures which make it difficult to determine which component or system needs to be trusted. This paper presents a novel trust measurement method for distributed systems which enables the t identification of weak points in the overall system architecture. The measurement method includes the specification of a formal trust language and its representation by means of propositional logic formulas. The applicability of the proposed concepts is demonstrated by conducting a case study on the Internet voting system that was used in the 2007 parliamentary elections in Estonia.
Keywords: distributed trust concepts; measuring etrust; Internet voting

Increasing software security through open source or closed source development? Empirics suggest that we have asked the wrong question - Schryen, Guido; Eliot, Rich (43rd Annual Hawaii International Conference on System Sciences)
While many theoretical arguments against or in favor of open source and closed source software development have been presented, the empirical basis for the assessment of arguments and the development of models is still weak. Addressing this research gap, this paper presents the first comprehensive empirical investigation of published vulnerabilities and patches of 17 widely deployed open source and closed source software packages, including operating systems, database systems, web browsers, email clients, and office systems. The empirical analysis uses comprehensive vulnerability data contained in the NIST National Vulnerability Database and a newly compiled data set of vulnerability patches. The results suggest that it is not the particular software development style that determines the severity of vulnerabilities and vendors? patching behavior, but rather the specific application type and the policy of the particular development community, respectively.

A decision-theoretic foundation of IS business value research - Schryen, Guido; Bodenstein, Christian (Proceedings of the 18th European Conference on Information Systems (ECIS 2010))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. Three research tasks are essential requisites on the path towards addressing this criticism: the synthesis of knowledge, the identification of lack of knowledge, and the proposition of paths for closing knowledge gaps. This paper considers each of these tasks by a) synthesizing key research findings based on a comprehensive literature review, b) identifying and unfolding key limitations of current research, and c) applying a decision-theoretic perspective, which opens new horizons to IS business value research and shows paths for overcoming the limitations. The adoption of this perspective results in a decision-theoretic foundation of IS business value research and includes the proposition of a consistent terminology and a research model that frames further research.
Keywords: Decision theory; IT value; IS assessment; IS evaluation

A Fuzzy Model for IT Security Investments - Schryen, Guido (Sicherheit 2010 : Sicherheit, Schutz und Zuverlässigkeit ; Konferenzband der 5. Jahrestagung des Fachbereichs Sicherheit der Gesellschaft für Informatik e.V. (GI), 5. - 7. Oktober 2010 in Berlin)
This paper presents a fuzzy set based decision support model for taking uncertainty into account when making security investment decisions for distributed systems. The proposed model is complementary to robabilistic approaches and useful in situations where probabilistic information is either unavailable or not appropriate to reliably predict future conditions. We ?rst present the speci?cation of a formal security language that allows to specify under which conditions a distributed system is protected against security violations. We show that each term of the security language can be transformed into an equivalent propositional logic term. Then we use propositional logic terms to de?ne a fuzzy set based decision model. This optimization model incorporates uncertainty with regard to the impact of investments on the achieved security levels of components of the distributed system. The model also accounts for budget and security constraints, in order to be applicable in practice.

An Analysis of Literature Reviews on IS Business Value: How Deficiencies in Methodology and Theory Use Resulted in Limited Effectiveness - Schryen, Guido (Proceedings of the First Scandinavian Conference on Information Systems (SCIS))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. This paper assumes that literature reviews, which represent a powerful instrument for the identification and synthesis of knowledge, have not tapped their full potential to address this issue due to deficiencies in methodology. The analysis of 18 literature reviews published in pertinent academic outlets during the past 20 years shows such deficiencies. Two of the most critical weaknesses identified are (1) the lack of theory use in most reviews and (2) a weak linkage of reviews, resulting in little progress in theory and framework development. The systematic identification of these weaknesses and the extraction of promising methodological examples from past literature are the main contributions of this work, which supports the composition of more effective literature reviews in future research.
Keywords: Literature review; Business value; Information systems; Methodology; Theory

Preserving knowledge on IS business value: what literature reviews have done - Schryen, Guido (Business & Information Systems Engineering (BISE))
The economic relevance of information systems has been studied for many years and has attracted an abundance of research papers. However, the ?productivity paradoxon? of the 90s, Carr?s widely recognized paper ?IT doesn?t matter?, and several studies that do not find a positive correlation between IS investments and economic performance reveal long-lasting difficulties for IS researchers to explain ?IS business value?. Business executives and researchers also continue to question the value of IS investments. This raises the question of whether literature reviews have tapped their potential to address the concerns by covering key research areas of IS business value and preserving their key findings. In order to address this question, this paper identifies and describes 12 key research areas, and synthesizes what literature reviews published in pertinent academic outlets have done to preserve knowledge. The analysis of 22 literature reviews shows that some crucial areas have not been (sufficiently) covered. They provide fertile areas for future literature reviews. As this work is based on the results of more than 200 research papers, it is capable of drawing a comprehensive picture of the current state-of-the-art in IS business value research.
Keywords: Business value; Information systems; Literature review; Meta review

Ökonomischer Wert von Informationssystemen - Beitrag von Literatur-Reviews zum Wissenserhalt ( = Preserving Knowledge on IS Business Value. What Literature Reviews Have Done) - Schryen, Guido (Wirtschaftsinformatik)
The economic relevance of information systems has been studied for many years and has attracted an abundance of research papers. However, the ?productivity paradoxon? of the 1990s, Carr?s widely recognized paper ?IT doesn?t matter?, and several studies that do not find a positive correlation between IS investments and economic performance reveal long-lasting difficulties for IS researchers to explain ?IS business value?. Business executives and researchers also continue to question the value of IS investments. This raises the question of whether literature reviews have tapped their potential to address the concerns by covering key research areas of IS business value and preserving their key findings. In order to address this question, this paper identifies and describes 12 key research areas, and synthesizes what literature reviews published in pertinent academic outlets have done to preserve knowledge. The analysis of 22 literature reviews shows that some crucial areas have not been (sufficiently) covered. They provide fertile areas for future literature reviews. As this work is based on the results of more than 200 research papers, it is capable of drawing a comprehensive picture of the current state-of-the-art in IS business value research.

Educational change and innovative teaching practice: a study of the impact of reforms on the work of lectures in vocational education and training in England and Germany - Ertl, H.; Kremer, H.-Hugo (Orbis Scholae, Educational Change in the global context)

Individuelle Förderung zur Kompetenzentwicklung in der beruflichen Bildung - Überlegungen zur Grundlegung eines Forschungs- und Entwicklungsbereichs - Kremer, H.-Hugo; Zoyke, A. (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Neue Medien als Katalysator individueller Förderung in der Berufsbildung - Kremer, H.-Hugo (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Individuelle Förderung im Reha-Vorbereitungslehrgang für besondere Zielgruppen - Entwicklung und Erprobung didaktisch-methodischer Reformsätze - Kremer, H.-Hugo; Zoyke, A. (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Individuelle Förderplanung - Rezeption und Einsatz im Übergangssystem - de Groot, C.; Kremer, H.-Hugo; Zoyke, A. (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Berufsorientierung als Herausforderung und Chance für die schulisch strukturierten Bildungsgänge des Übergangssystems - Kremer, H.-Hugo (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Wie der Übergang gelingen kann - Empirische Explorationen zur beruflichen Orientierung von Jugendlichen im Übergangssystem - Kremer, H.-Hugo; Rüschen, E. (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Kollektivstrukturen als Gestaltungselemente in der wirtschaftspädagogischen Begleitforschung - Beutner, Marc; Kremer, H.-Hugo (Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten)

Modellbasierte Bestimmung lokal gültiger Kinetiken chemischer Reaktionen in Flüssigphase mittels Flachbettmikroreaktor* - Warnecke, H.-J.; Bothe, D.; Zrenner, Artur; Berth, Gerhard; Hüsch, K.-P. (Chemie Ingenieur Technik)
Strömungsbasierte Mischprozesse sind grundlegender Bestandteil vieler chemischer Prozesse. Realisierbare Mischzeiten reichen von einigen Millisekunden bis zu Sekunden, wobei die vollständige Homogenisierung oft nicht sichergestellt ist. Werden kinetische Parameter chemischer Reaktionen dieses Zeitskalenbereichs ohne Berücksichtigung der Mischprozesse bestimmt, sind sie mischungsmaskiert und geben die inhärente chemische Kinetik nicht wieder. In dieser Arbeit wird die Validierung und Anwendung einer Methode zur Bestimmung inhärenter chemischer Kinetiken von in Flüssigphase ablaufenden chemischen Reaktionen im stationären, laminaren Flachbettmikroreaktor vorgestellt. Der verfolgte Ansatz basiert auf der mechanistischen Modellierung der Molmengen unter Berücksichtigung von Konvektion, Diffusion und Reaktion und der Bestimmung der unbekannten Parameter durch Anpassung des Modells an experimentell ermittelte Konzentrationsverläufe.

Reading British Spaces

Das englische Drama der Gegenwart: Kategorien-Entwicklungen-Modellnterpretationen

The Features of Meanings of Orality in Black British Performance Poetry - Tönnies, Merle; Sand, Andrea (Anglistentag 2009 Klagenfurt. Proceedings)